MĚSTSKÝ DŮM NA NÁBŘEŽÍ V PŘEROVĚ - Juráň, Petr (Vysoké učení technické v Brně. Fakulta architektury)
Daný stavební pozemek se nachází na nábřeží v moravském městě Přerov, který je v blízkosti historického centra oddělen řekou. Návrh objektu urbanisticky napravuje a doplňuje nesprávnou uliční čáru. Koncept stavby vychází z historie, měřítka města a nárožní polohy pozemku. Koncept svojí hmotou reaguje na měřítko města i okolní zástavbu. Historie města se projevuje ve fasádě (při členění otvorů) jako reakce na neuspořádaný urbanistický vývoj města. Náplň v podobě obchodů a bydlení vyššího standardu ctí výjimečnou nárožní polohu nad řekou s výhledem na historické centrum.

The construction site is located on the waterfront in the Moravian town of Prerov, which is near the historical center of the river separated. Proposal for building urban and supplements to correct the wrong street line. The concept is based on the construction history, the scale of the city and corner plot location. His concept of matter responds to the scale of the city and surrounding buildings. The city's history is reflected in the facade (the breakdown of holes) in response to disorderly urban development of cities. Filling in the form of housing, shops and a higher standard of honor exceptional corner position overlooking the river overlooking the historic center.
TOWNHOUSE ON THE WATERFRONT IN PŘEROV
Keywords: nárožní dům nábřeží přerov; corner house watercoast prerov